Penerapan IPV4 dan IPV6 pada Jaringan yang Terhubung - Afrizal Afrizal; Fitriani Fitriani (KITA Institute, 2019)
The computer networks is growing rapidly along with the increasing of computer's users. The large number of computers or hosts connected in a network will make it difficult to manage, so it needs a unique identity on each host connected to a computer network. The IP address technology is a solution to overcome the complexity of local and global computer networks. The IPv4 is the IP addressing technology for every host connected in a network, but the growth of computer users hence the availability of IPv4 address becomes very limited, so the IPv6 technology is developed. To avoid IP address conflicts around the world, the IP address allocation and distribution blocks for each Internet service providers worldwide is arranged by RFC (Request for Comments) standards. This journal describes the IPv4 and IPv6 addresses technology implementation on the host connected in a computer network. It is expected that with this journal both IP addresses generation can be applied in a computer network appropriately.